A national profile of health-focused caregiving activities prior to a new cancer diagnosis. Issue 4 (May 2022) - Liu, Bian; Kent, Erin E.; Dionne-Odom, J. Nicholas; Alpert, Naomi; Ornstein, Katherine A.
Abstract: Background: Little is known about how unpaid family caregivers may already be engaged in caregiving activities prior to their care recipient's cancer diagnosis. We examined pre-cancer diagnosis caregiving patterns and their association with caregiving strain. Methods: We conducted a population-based analysis of 2011–2017 National Health and Aging Trends Study (NHATS) linked with the National Study of Caregiving (NSOC) and Medicare claims data. Latent class analysis was used to examine patterns of 16 health-focused caregiving tasks (e.g., tracking medications, making appointments) of family caregivers assisting adults ≥65 years prior to an incident cancer diagnosis. High caregiving strain was defined as a total score ≥ 85th percentile of 6 caregiving strain items (e.g., financial difficulty, no time for self). Association between caregiving patterns and strain were examined using multivariable logistic regression, adjusting for care recipient and caregiver characteristics. Results: An estimated 4.2 million caregivers cared for older adults prior to care recipients' new cancer diagnoses during 2011–2017. They engaged in a median of four health-focused caregiving activities. Nearly 1-in-5 (18.7%) pre-cancer caregivers had high caregiving strain. Caregivers were classified into 3 health-focused caregiving activity classes: Low-level (41.2%), Moderate-coordination (29.3%), and High-intensity (29.4%). Higher caregiving activity was associated with higher caregiving strain (adjusted odds ratio (aOR) = 3.85, 95% CI: 2.34–6.33). Caregivers in the High-intensity class had the highest caregiving strain (39.9%), and included more spouses (28.1% vs <18%). Conclusion: One-third of U.S. caregivers who help older adults prior to their cancer diagnoses are already highly strained and engaged in high-level health-focused caregiving tasks. Oncology clinicians should assess the capacity and strain of family caregivers who may already be supporting patients with new cancer diagnoses and refer caregivers to additional supportive care services.